2018
DOI: 10.1016/j.scr.2018.04.005
|View full text |Cite|
|
Sign up to set email alerts
|

Generation of induced pluripotent stem cells from a patient with X-linked juvenile retinoschisis

Abstract: X-linked juvenile retinoschisis (XLRS) is a hereditary retinal dystrophy manifested as splitting of anatomical layers of retina. In this report, we generated a patient-specific induced pluripotent stem cell (iPSC) line, TVGH-iPSC-013-05, from the peripheral blood mononuclear cells of a male patient with XLRS by using the Sendai-virus delivery system. We believe that XLRS patient-specific iPSCs provide a powerful in vitro model for evaluating the pathological phenotypes of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…At least two independent hiPSC clonal lines were generated from each XLRS patient or control donor, and all control-donor- and patient-derived hiPSC clones exhibited normal karyotypes and expressed human PSC markers (Figures S2A–S2C). Genotyping of the XLRS patient-derived hiPSC clones confirmed the presence of the respective RS1 mutations at c.625C>T and c.488G>A (Figure 1B) (Peng et al., 2018). We then applied a stepwise three-dimensional (3D) retinal organoid formation protocol (Figure 1C) (Ohlemacher et al., 2015, Zhong et al., 2014) on the hiPSCs of control donors (Ctrl-1 and Ctrl-2) and XLRS patients (Pt-1 and Pt-2) to generate 3D retinal organoids.…”
Section: Resultsmentioning
confidence: 92%
“…At least two independent hiPSC clonal lines were generated from each XLRS patient or control donor, and all control-donor- and patient-derived hiPSC clones exhibited normal karyotypes and expressed human PSC markers (Figures S2A–S2C). Genotyping of the XLRS patient-derived hiPSC clones confirmed the presence of the respective RS1 mutations at c.625C>T and c.488G>A (Figure 1B) (Peng et al., 2018). We then applied a stepwise three-dimensional (3D) retinal organoid formation protocol (Figure 1C) (Ohlemacher et al., 2015, Zhong et al., 2014) on the hiPSCs of control donors (Ctrl-1 and Ctrl-2) and XLRS patients (Pt-1 and Pt-2) to generate 3D retinal organoids.…”
Section: Resultsmentioning
confidence: 92%
“…The studies of optic neuropathies caused by genetic determinants using hPSCs are of particular interest as they are the result of known mutations, which allow for a more direct connection of cellular changes to a particular phenotype [5,7]. Patient-specific hPSCs can be differentiated into retinal cell types such as photoreceptors and RPE in a consistent and reproducible manner to study retinal degenerative disorders that cause damage to more outer retinal cell types, with the remarkable ability to use such cells for drug screening, cell replacement, and targeted therapeutics [11,12,[20][21][22][23][24][25][26][27]. Such studies have conducted thorough and in-depth experiments that have identified specific cellular changes in outer retinal cell types such as oxidative and ER stress, autophagy deficits, alterations in protein trafficking, and phagocytotic defects associated with disease-causing mutations.…”
Section: Applications Of Hpscsmentioning
confidence: 99%
“…Induced pluripotent stem cell (iPSC) technologies have been shown to hold great promise for personalized therapy, translation medicine, and regeneration medicine [1]. Owing to the potential of iPSCs to be generated from somatic cells via the transduction of specific transcription factors [2], scientists reprogrammed patient-derived somatic cells to generate patient-specific iPSCs [3][4][5]. Remarkably, silencing the expression of human leukocyte antigen (HLA) class I allows to establish the universal human leukocyte antigen 2 of 18 (HLA) iPSCs characterized by low immunogenicity [6].…”
Section: Introductionmentioning
confidence: 99%